Transporte de material em suspensão e dissolvido em modelo físico com superfície impermeável utilizando chuva simulada - Felice, Jéssica Giacchetto (2017)
The accelerated process of urbanization has given to perceive, from the second half of XX century, several land changes as a consequence of the development of anthropic activities. These changes are capable of compromising the balance and quality of natural resources, in particular, of water resources. The decrease in evapotranspiration and infiltration, the increased frequency of floods in urban areas and the degradation of water bodies are some examples of these impacts. The development of anthropic activities and the disorganized occupation of the soil contributes to the introduction and accumulation of contaminant materials in the ecosystems, which, in rainy periods, are transported by surface runoff –a major cause of diffuse pollution. Therefore, the objective of this work is to study experimentally the transport of pollutants from diffuse sources, by testing several origin-points of pollution in relation to the outlet of an impervious surface, as well as testing suspended and dissolved pollutants, represented by particles of fine sand and sodium chloride, respectively. The experimental setup consists of a rainfall simulator placed over a rectangular acrylic impervious surface with 8,40 m², divided into four regions, where fine sand and sodium chloride are placed. The results showed higher peak mass discharges for the transport of dissolved material, as well as a shorter time to peak, when compared to the transport of pollutants in suspension. The first-flush effect was observed in all the regions for the transport of sodium chloride, while the transport of fine sand led to this effect only in the regions closest to the outlet of the surface. The similarity in the behaviour of the transport of suspended and dissolved pollutants in the regions closer to the outlet, shows the dependence of these processes from the energy of runoff, which in this experiments was enough to drag the particles placed in the impervious surface.